A First Aid Information Mobile Application. - Kabere, July Smith (Kabale University, 2024)
Lack of Knowledge about first aid applications among people caused by lack of awareness and inability to find real-time information concerning the cause of the illness. Many people neglect the correct ways of administering the right first aid procedures when an emergency happens. As a result, this causes many complications such as the risk of possible bacterial infection, paralysis, and other severe infections if the wrong procedures of first aid are being administered to the victim. This therefore necessitates a First Aid Information Mobile Application that would provide tips and information regarding the application of first aid to different patients and later provide a fast hospital location for better medication. The purpose of this study was to develop an android mobile application that will provide real-time information on how to apply first aid by any nearby persons to different causalities.